Correlation of serpin–protease expression by comparative analysis of real-time PCR profiling data - Badola, Sunita; Spurling, Heidi; Robison, Keith; Fedyk, Eric R.; Silverman, Gary A.; Strayle, Jochen; Kapeller, Rosana; Tsu, Christopher A. (Genomics (San Diego, Calif.), 2006)
Imbalanced protease activity has long been recognized in the progression of disease states such as cancer and inflammation. Serpins, the largest family of endogenous protease inhibitors, target a wide variety of serine and cysteine proteases and play a role in a number of physiological and pathological states. The expression profiles of 20 serpins and 105 serine and cysteine proteases were determined across a panel of normal and diseased human tissues. In general, expression of serpins was highly restricted in both normal and diseased tissues, suggesting defined physiological roles for these protease inhibitors. A high correlation in expression for a particular serpin–protease pair in healthy tissues was often predictive of a biological interaction. The most striking finding was the dramatic change observed in the regulation of expression between proteases and their cognate inhibitors in diseased tissues. The loss of regulated serpin–protease matched expression may underlie the imbalanced protease activity observed in pathological states.